Perubahan Relasi Gender di Ruang Kerja Digital berdasarkan Analisis Ilmu Sosial Aktual - Hamidah, Fanda; Hartanto, Rully; Hadi, Komaruddin (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
Work digitalization has reshaped organizational structures, interaction patterns, and decision-making mechanisms in the workplace, while simultaneously reconfiguring gender relations in complex ways. This study aims to analyze changes in gender relations within digital workspaces through a synthesis of contemporary social science perspectives, integrating feminist technology theory, sociology of work, and organizational studies. The research adopts a qualitative approach with a critical conceptual analysis design based on a systematic literature review of relevant international scholarly works. Data were analyzed through thematic coding and conceptual synthesis to identify patterns of reproduction, negotiation, and transformation of gender relations in contemporary digital work practices. The findings indicate that digital workspaces are not gender-neutral. Digitalization tends to reproduce gender inequalities through new mechanisms such as algorithmic management, technology-based performance evaluation, and uneven demands for flexibility. Digital work flexibility expands opportunities for participation, yet simultaneously intensifies work and reinforces double burdens, particularly for women. Gender discrimination does not disappear in digital contexts but rather transforms into more subtle and technologically legitimized forms. At the same time, digitalization opens spaces for negotiating gender identities and redefining work competencies, although outcomes remain highly dependent on organizational contexts and workplace cultures. This study demonstrates that changes in gender relations in digital workspaces constitute a dynamic social process mediated by organizational structures, policies, and technological practices. The findings contribute to the development of a critical analytical framework for understanding the social implications of work digitalization and highlight the importance of gender-sensitive approaches in digital transformation processes.